(NgOLXBAH I SOWREMENNOSTX (B/s - d; (NnAWASARDQN(B, (Nr(B.(Ng(B.s ((NeREWAN (B:s (NaJASTAN(B,s, 1987)
(NrEZ@ME(B: (NARM(B., (NANGL(B.s
(NuKAZ(B. (NIMEN(B: (NS(B. 284-287s
(NbIBLIOGR(B.: (NS(B. 288-292s
Keywords: (NgOLXBAH(B, (NpOLXs; (NfILOSOFIQs